Effect of Rubber Thickness on the Performance of Conventional Solar Stills under El Oued city climate (Algeria) - Kermerchou, Imad; Khechekhouche, Khechekhouche; Elsharif, Nabil (جامعة الوادي Université ofEl-Oued, 2023)
Our study focuses on examining the performance of conventional solar stills in an arid region, specifically investigating the impact of rubber material and its thickness on the distillation process. Four solar stills were tested, including a reference solar still (SSR) and three modified solar stills (MSS1, MSS2, and MSS3) with rubber thicknesses of 1 cm, 2 cm, and 3 cm, respectively. The experimental findings clearly demonstrate a notable difference in distilled water productivity between varying rubber thicknesses. The outputs of MSS1, MSS2, and MSS3 were measured at 1105 ml/day, 1010 ml/day, and 955 ml/day, respectively, all surpassing the output of SSR, which was recorded at 830 ml/day. These results indicate that the utilization of rubber with varying thicknesses positively impacts the productivity of the solar still, leading to higher distilled water yields compared to the reference configuration
Article
Keywords: Solar energy, Water productivity, Salty water, Solar radiation